The Effective M3Y Residual Interaction In 41Ca As a Nuclear Diffraction Grating of Electrons (Baghdad Science Journal, 2022)
The total and individual multipole moments of  magnetic electron scattering form factors in 41Ca  have been investigated using a widely successful model which is the nuclear shell model configurations keeping in mind of 1f7/2 subshell as an L-S shell and Millinar, Baymann, Zamick as L-S shell (F7MBZ) to give the model space  wave vector. Also, harmonic oscillator wave functions have been used as wave function of a single particle in 1f7/2  shell. Nucleus 40Ca as core closed and Core polarization effects have been used as a corrective with first order correction concept to basic computation of L-S shell and the excitement energy has been implemented with 2ћω. The core polarizability effect has been utilized to incorporate the rejected space (core + higher arrangement) via L-S shell with a realism interaction of effective M3Y P2 interaction to connect the model space particles in motion with the spouse (p-h). The two body M3Y interactions have been utilized as an interaction residue to calculate the core polarizability matrix elements. Finally, the theoretical result of the form factor has been compared with the experimental results.